التمييز دراسة تحليلية في البنية - وقاف حسين; حبيب ماهر; عبد الحليم فراس (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يدرس هذا البحث البنية اللغوية للتمييز، فيحلل علاقاته التركيبية وما يتصل بها من ظواهر صرفية وصوتية، ويستند في الدراسة إلى علمي البلاغة والدلالة. فهو يبين معنى التمييز ونوعيه، ويدرسه كأحد المنصوبات التركيبية؛ مندرجاً تحت ما يسمى الإعراب الدلالي المبوب، كما يدرس انتصاب التمييز والعلامة الصوتية له ويدرس كذلك التمييز المجرور، ويُعنى أيضاً بدراسة التمييز من حيث الرتبة، ومن حيث وقوع الحذف عليه في السياق اللغوي، ويسلط الضوء على دلالة تحوّل التمييز عن أصله، كما يوضّح سمات التمييز، ويستقرئ علامته، وهي انتصابه عن عامل منكر، وهو أيضاً يقرأ التمييز وفق رؤية تجريدية تنسجم مع روح اللغة والفكر الذي تقوم عليه، ليغدو التمييز بذلك بنية تجريدية إلى جانب كونه بنية لغوية. This research studies the linguistic structure of al-tameez. It analyzes its structural relationships and the related morphological and vocal phenomenon, using the sciences of eloquence and conducting. It shows the meaning of al-tameez and its two types. It studies it as one of the structural accusative classified in what is called the indicative categorized syntax. Moreover, it studies the accusative – nasb – of al-tameez and its phonetic sign. It also studies genitive tameez. Besides, it studies al-tameez concerning level and deletion within the linguistic context. It throws light upon the indication of the transformation of al-tameez from its origin. Furthermore, it clarifies the characteristics of al-tameez, and examines its mark: the accusative mark – nasb – because of an indefinite agent. It also investigates al-tameez according to an abstract point of view which gets along with the essence of language and the intellect upon which it is based. Therefore, al-tameez is an abstract structure besides being a linguistic structure.